Pharmacokinetics, Safety, and Clinical Efficacy of Cannabidiol Treatment in Osteoarthritic Dogs - Gamble, Lauri-Jo; Boesch, Jordyn M.; Frye, Christopher W.; Schwark, Wayne S.; Mann, Sabine; Wolfe, Lisa; Brown, Holly; Berthelsen, Erin S.; Wakshlag, Joseph J. (Frontiers in Veterinary Science, 2018)
ABSTRACT Objectives The objectives of this study were to determine basic oral pharmacokinetics, and assess safety and analgesic efficacy of a cannabidiol (CBD) based oil in dogs with osteoarthritis (OA). Methods Single-dose pharmacokinetics was performed using two different doses of CBD enriched (2 mg/kg and 8 mg/kg) oil. Thereafter, a randomized placebo-controlled, veterinarian and owner blinded, cross-over study was conducted. Dogs received each of two treatments: CBD oil (2 mg/kg) or placebo oil every 12 hours. Each treatment lasted for 4 weeks with a 2-week washout period. Baseline veterinary assessment and owner questionnaires were completed before initiating each treatment and at weeks 2 and 4. Hematology, serum chemistry and physical examinations were performed at each visit. A mixed model analysis was utilized for all variables with a p value of < 0.05 deemed significant. Results Pharmacokinetics revealed an elimination half-life of 4.2 hours at both doses and no observable side effects. Clinically, canine brief pain inventory and Hudson activity scores showed a significant decrease in pain and increase in activity (p < 0.01) with CBD oil. Veterinary assessment showed decreased pain during CBD treatment (p < 0.02). No side effects were reported by owners, however, serum chemistry showed an increase in alkaline phosphatase during CBD treatment (p < 0.01). Clinical significance This pharmacokinetic and clinical study suggests that 2 mg/kg of CBD twice daily can help increase comfort and activity in dogs with OA. Keywords Cannabidiol; CBD oil; hemp; canine; osteoarthritis; pharmacokinetic